Understanding Organizational Citizenship Behavior: The Roles of Personality, Work Engagement, and Work Motivation - Defi Cynthia Dewi; Rokiah Kusumapradja; Duta Liana; Noorsidi Aizuddin Bin Mat Noor (International Journal of Economics, Management and Accounting, 2026)
This study examines the impact of personality and work engagement on Organizational Citizenship Behavior (OCB), with work motivation serving as a mediating variable, among inpatient nurses at South Jakarta Type B Hospital. OCB is crucial for enhancing organizational performance and service quality, especially in healthcare settings, where nurses' extra-role behaviors significantly contribute to patient care. The research utilized a quantitative approach with a survey design, involving 143 nurses from infection and critical inpatient wards. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that personality positively influences both work motivation and OCB. Work engagement also positively impacts work motivation and OCB. Additionally, work motivation significantly affects OCB and partially mediates the relationship between personality, work engagement, and OCB. These findings suggest that fostering nurses' work engagement and motivation, supported by positive personality traits, can enhance OCB, leading to better organizational performance and improved healthcare service quality.